TI_GERICHTE 52.2018.180 vom 7. März 2018 , Revoca della licenza di condurre a causa di inidoneità. Riammissione alla guida - TI Tribunale d'appello (2018)
Revoca della licenza di condurre a causa di inidoneità. Riammissione alla guida